Inhibition of NK1.1 signaling attenuates pressure overload-induced heart failure, and consequent pulmonary inflammation and remodeling - He, Xiaochen; Xu, Rui; Pan, Lihong; Bhattarai, Umesh; Liu, Xiaoguang; Zeng, Heng; Chen, Jian-Xiong; Hall, Michael E.; Chen, Yingjie (Frontiers in Immunology, 2023)
Background Inflammation contributes to heart failure (HF) development, the progression from left ventricular failure to pulmonary remodeling, and the consequent right ventricular hypertrophy and failure. NK1.1 plays a critical role in Natural killer (NK) and NK T (NKT) cells, but the role of NK1.1 in HF development and progression is unknown. Methods We studied the effects of NK1.1 inhibition on transverse aortic constriction (TAC)-induced cardiopulmonary inflammation, HF development, and HF progression in immunocompetent male mice of C57BL/6J background. Results We found that NK1.1+ cell-derived interferon gamma+ (IFN-γ+) was significantly increased in pulmonary tissues after HF. In addition, anti-NK1.1 antibodies simultaneously abolished both NK1.1+ cells, including the NK1.1+NK and NK1.1+NKT cells in peripheral blood, spleen, and lung tissues, but had no effect on cardiopulmonary structure and function under control conditions. However, systemic inhibition of NK1.1 signaling by anti-NK1.1 antibodies significantly rescued mice from TAC-induced left ventricular inflammation, fibrosis, and failure. Inhibition of NK1.1 signaling also significantly attenuated TAC-induced pulmonary leukocyte infiltration, fibrosis, vessel remodeling, and consequent right ventricular hypertrophy. Moreover, inhibition of NK1.1 signaling significantly reduced TAC-induced pulmonary macrophage and dendritic cell infiltration and activation. Conclusions Our data suggest that inhibition of NK1.1 signaling is effective in attenuating systolic overload-induced cardiac fibrosis, dysfunction, and consequent pulmonary remodeling in immunocompetent mice through modulating the cardiopulmonary inflammatory response.